The Autobiography of an Orange Seller - Ikogho, Eric (Book collections on Project MUSE., 2015)
This autobiography relives the lifestyle of a Warri Boy, the typical escapades of a young man going through life with the influence of peer groups, and an ultimate transformation through experiences of self-discovery and a deepening relationship with God.